m6A-dependent glycolysis enhances colorectal cancer progression - Chaoqin Shen; Baoqin Xuan; Tingting Yan; Yanru Ma; Pingping Xu; Xianglong Tian; Xinyu Zhang; Yingying Cao; Dan Ma; Xiaoqiang Zhu; Youwei Zhang; Jing-Yuan Fang; et al. (Molecular Cancer, 2020)
Abstract Background Epigenetic alterations are involved in various aspects of colorectal carcinogenesis. N 6-methyladenosine (m6A) modifications of RNAs are emerging as a new layer of epigenetic regulation. As the most abundant chemical modification of eukaryotic mRNA, m6A is essential for the regulation of mRNA stability, splicing, and translation. Alterations of m6A regulatory genes play important roles in the pathogenesis of a variety of human diseases. However, whether this mRNA modification participates in the glucose metabolism of colorectal cancer (CRC) remains uncharacterized. Methods Transcriptome-sequencing and liquid chromatography-tandem mass spectrometry (LC-MS) were performed to evaluate the correlation between m6A modifications and glucose metabolism in CRC. Mass spectrometric metabolomics analysis, in vitro and in vivo experiments were conducted to investigate the effects of METTL3 on CRC glycolysis and tumorigenesis. RNA MeRIP-sequencing, immunoprecipitation and RNA stability assay were used to explore the molecular mechanism of METTL3 in CRC. Results A strong correlation between METTL3 and 18F-FDG uptake was observed in CRC patients from Xuzhou Central Hospital. METTL3 induced-CRC tumorigenesis depends on cell glycolysis in multiple CRC models. Mechanistically, METTL3 directly interacted with the 5′/3’UTR regions of HK2, and the 3’UTR region of SLC2A1 (GLUT1), then further stabilized these two genes and activated the glycolysis pathway. M6A-mediated HK2 and SLC2A1 (GLUT1) stabilization relied on the m6A reader IGF2BP2 or IGF2BP2/3, respectively. Conclusions METTL3 is a functional and clinical oncogene in CRC. METTL3 stabilizes HK2 and SLC2A1 (GLUT1) expression in CRC through an m6A-IGF2BP2/3- dependent mechanism. Targeting METTL3 and its pathway offer alternative rational therapeutic targets in CRC patients with high glucose metabolism.